2017
DOI: 10.14814/phy2.13347
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke differentially affects IL-13-induced gene expression in human airway epithelial cells

Abstract: Allergic airways inflammation in asthma is characterized by an airway epithelial gene signature composed of POSTN,CLCA1, and SERPINB2. This Th2 gene signature is proposed as a tool to classify patients with asthma into Th2‐high and Th2‐low phenotypes. However, many asthmatics smoke and the effects of cigarette smoke exposure on the epithelial Th2 gene signature are largely unknown. Therefore, we investigated the combined effect of IL‐13 and whole cigarette smoke (CS) on the Th2 gene signature and the mucin‐rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 44 publications
6
28
0
Order By: Relevance
“…Short-term exposure to cigarette smoke has been found to induce a Th2 inflammatory response, increasing the concentration of IL-13 and differentially affecting the IL-13-induced expression profile, including the marked down-regulation of periostin ( POSTN ) gene expression, as in Th2-high phenotype asthma. 17 In addition, an epidemiological study showed that chronic exposure to high levels of VOCs was significantly associated with reduced serum IL-13 concentrations. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Short-term exposure to cigarette smoke has been found to induce a Th2 inflammatory response, increasing the concentration of IL-13 and differentially affecting the IL-13-induced expression profile, including the marked down-regulation of periostin ( POSTN ) gene expression, as in Th2-high phenotype asthma. 17 In addition, an epidemiological study showed that chronic exposure to high levels of VOCs was significantly associated with reduced serum IL-13 concentrations. 18 …”
Section: Discussionmentioning
confidence: 99%
“…1 Basophils also express IL-5Rα, participate in T2-mediated inflammatory pathways 2 and have been associated with exacerbation frequency. [5][6][7][8] Our primary objective was to determine whether anti-IL-5 monoclonal antibody treatment reduces blood basophil levels as an additional potential efficacy mechanism. [5][6][7][8] Our primary objective was to determine whether anti-IL-5 monoclonal antibody treatment reduces blood basophil levels as an additional potential efficacy mechanism.…”
Section: Mepolizumab Does Not Alter the Blood Basophil Count In Severmentioning
confidence: 99%
“…Following Cincinnati Children's Hospital Medical Center (CCHMC) IRB approval, children (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years old) with physician-diagnosed asthma were enrolled in the Pediatric Environmental Exposure Study (PEES). 4 Children and parents completed surveys to assess current secondhand smoke (SHS) exposure, early maternal smoking, asthma symptom frequency over the past 4 weeks (wheeze, shortness of breath, cough, and chest tightness), asthma control (childhood Asthma Control Test [ACT]), medication usage/treatment step, and exposure to air pollutants based on estimated mean concentration of elemental carbon attributable to traffic (ECAT) exposure using birth and current address.…”
Section: Age and Early Maternal Smoking Contribute To Epithelial Cellmentioning
confidence: 99%
See 2 more Smart Citations